A wrinkle in time - Larson, Hope.; L'Engle, Madeleine (New York : Farrar Straus Giroux, 2012)
A graphic novel adaptation of the classic tale in which Meg Murry and her friends become involved with unearthly strangers and a search for Meg's father, who has disappeared while engaged in secret work for the government.
"Margaret Furguson Books."
Keywords: Graphic novels; Science fiction